Tissues thiocyanate (SCN) concentration and liver pathology of sheep and goats fed on cassava forages - Shaari, Mohd Rosly; Liang, Juan Boo; Mohamed Mustapha, Noordin; Somchit, Muhammad Nazrul Hakim; Mohd Jelan, Zainal Aznam (Universiti Putra Malaysia Press, 2010)
Cassava leaves are good sources of protein which have a potential to substitute grain concentrate in livestock feed. However, a major constraint in using cassava fodder as animal feed is the presence of hydrogen cyanide (HCN). A study was conducted to compare the cumulative effects of thiocyanate (a product from the detoxification of hydrogen cyanide) at 4 mg and 7 mg HCN/ kg body weight on sheep and goats. Thiocyanate was sourced from the detoxification of hydrogen cyanide in cassava. The tissue thiocyanate concentrations were found to be significantly (p<0.05) higher in liver (2.29 μg/mL/g tissue) of goats as compared to that of sheep. Meanwhile, histological examination of the liver revealed the presence of periportal necrosis. In spite of detoxification process of hydrogen cyanide to thiocyanate, it could be concluded that at 7 mg HCN/kg body weight, considerable amount of thiocyanate was retained in the body and accumulated in the liver.